Another economic miracle? The German labor market and the great recession - Ulf Rinne; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2011)
The mild response of the German labor market to the worst global recession in post-war history appears as an economic miracle. In response to the crisis, Germany has shown to be a strong case of internal flexibility. We argue that important factors that have contributed to this development include the strong position of the German economy due to recent labor market reforms, the nature of the crisis affecting mainly export-oriented companies in Germany, the extension of short-time work, the behavior of social partners, and automatic stabilizers. Among these factors, we emphasize the key role of the interaction between short-time work and long-term shortages of skilled workers in sectors and regions that were particularly affected by the crisis. Although the German experience is in stark contrast to that in the United States, we identify and discuss three challenges that will be at the center of debate on both sides of the Atlantic in the future.
urn:nbn:de:101:1-201203016120
Keywords: J68; J21; P52; O57; 330; economic crisis; Germany; short-time work; unemployment; labor market institutions; internal flexibility; Wirtschaftskrise; Arbeitslosigkeit; Arbeitsmarktflexibilität; Unterbeschäftigung; Qualifikationsbedarf; Deutschland